Sensitivity of enzyme-linked immunosorbent assay, complement fixation, and hemagglutination inhibition serological tests for detection of Sendai virus antibody in laboratory mice. - Parker, J C (1979)
The enzyme-linked immunosorbent assay technique for detection of Sendai virus antibody in mice was approximately 100- and 300-fold more sensitive than the complement fixation and hemagglutination inhibition tests, respectively. The assay also permitted direct quantitative measurement of the amount of antibody on a single serum dilution rather than by the more traditional serial titration.